ANALISIS AKUNTABILITAS DAN TRANSPARANSI DALAM PENGELOLAAN KEUANGAN MASJID AL-AHSANI KEC. SUNGGAL KAB.DELI SERDANG - Muhammad Kholid Adfi; Nurwani Nurwani; Yenni Samri Juliati Nasution (POLITEKNIK LP3I JAKARTA, 2023)
The purpose of this research is to improve the financial accountability and transparency of the Al-Ahsani Mosque. The research method is descriptive qualitative. Documentation, field observation, observation, and interviews were used to obtain data with two informants related to Al-Ahsani Mosque, namely the mosque chairman and the mosque treasurer. The investigation method applied is a case study. The results showed a positive attitude towards the responsibility given to mosque administrators in carrying out non-profit (mosque) financial policies. Transparency in mosque financial management is still not fully implemented in transparency in financial management reporting. It's just that the transparency implemented by the mosque is in the form of announcing the records of the mosque's financial statements every Friday in person. Key words: Financial Reporting, Accountability, Transparency